Vasculitis and familial Mediterranean fever: Description of 22 French adults from the juvenile inflammatory rheumatism cohort - Abbara, Salam; Monfort, Jean-Benoit; Savey, Léa; Moguelet, Philippe; Saadoun, David; Bachmeyer, Claude; Fain, Olivier; Terrier, Benjamin; Amoura, Zahir; Mathian, Alexis; Gilardin, Laurent; Buob, David; et al. (Frontiers in Medicine, 2022)
Objective: The frequency of vasculitis may be increased in patients with Familial Mediterranean Fever (FMF), according to several studies. Our aim was to assess the characteristics of French adult patients with both diseases. Methods: Patients with vasculitis were selected from patients followed for FMF in the French JIR cohort. Results: Twenty-two patients were included (polyarteritis nodosa (PAN) n=10, IgA vasculitis n=8, unclassified vasculitis n=2, granulomatosis with polyangiitis n=1, microscopic polyangiitis n=1). Pathogenic mutations in exon 10 were found in all 21 patients (96%) for which MEFV testing results were available, and 18 (82%) had two pathogenic mutations. Histology showed vasculitis in 59% of patients. Most patients with FMF-associated PAN were HBV negative and had an inactive FMF before PAN onset, and 40% had a perirenal or central nervous system bleeding. Most patients with FMF-associated IgA vasculitis had an active FMF before vasculitis onset, and 25% had digestive bleeding. Both patients with unclassified vasculitis had ischemic and/or hemorrhagic complications. Conclusion: This study confirms the predominance of PAN and IgA vasculitis in patients with FMF and the high frequency of bleeding in FMF-associated PAN. FMF should be considered in case of persistent symptoms and/or inflammatory syndrome despite vasculitis treatment in Mediterranean patients.